The Effect of Conservatism Accounting and Tax Risk on Firm Value: Agency Costs as a Moderating Factor - Korniawati, Linda; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of accounting conservatism and tax risk with agency cost as moderators in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population in this study is energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This study uses a purposive sampling technique, obtained from 8 companies so that the number of samples used is 40 observation data. The analysis used in this study is multiple regression analysis using SPSS version 26 as a calculation tool. Based on the results in this study, it shows that tax risk has no effect on the value of the company. Meanwhile, accounting conservatism shows a negative effect on the value of the company. Agency cost fully reinforce the relationship of accounting conservatism to the value of the company, but agency cost cannot moderate the tax risk to the value of the company.